Formulation of Novel Composite (Activated Nanoclay/Hydrocolloid of Nostoc sphaericum) and Its Application in the Removal of Heavy Metals from Wastewater - Choque Quispe, David (2022)
The removal of heavy metals from wastewater is an environmental challenge which demands the use of environmentally friendly materials that promote a circular economy. This study aimed to apply a novel composite of an activated nanoclay/hydrocolloid in the removal of heavy metals from wastewater. A composite blended under pressure was prepared with spray-dried hydrocolloid derived from Nostoc sphaericum algae and activated nanoclay in an acid medium and 1M NaCl. The composite and components were analyzed through infrared (IR), X-ray (XR), ζ potential, cation exchange capacity (CEC), particle size, and SEM images. The composite was subjected to the adsorption of heavy metals (Pb, As, Zn, and Cd) at pH 4.5 and the removal percentage, kinetics, and adsorption isotherms were evaluated. It was observed that the activated nanoclay and the composite that presented a particle size of around 400 nm significantly increased (p-value < 0.05) the CEC, ζ potential, the functional groups, and chelating components, removing heavy metals above 99% for Pb, As 33%, Cd 15%, and Zn 10%. Adsorption kinetics was adjusted to the pseudo second-order model (R 2 > 0.98), and the Langmuir and Freundlich models better represented the sorption isotherm at 20 ◦C. The formulated composite presents a good ability to remove heavy metals in wastewater